Modelling and parameter estimation of dynamic systems - Raol, J. R. (Jitendra R.) 1947-; Girija, G. 1954- (Gopalrathnam).; Singh, J. Ph.D. (London, United Kingdom Institution of Engineering and Technology, 2004)
The book is written at postgraduate level and comprised N chapters dealing with the following topics: modelling; parameter estimation; dynamic systems; least squares method; output error method; filtering methods; filter error method; model error determination; and model error concept.
Electronic reproduction.
Keywords: Systems engineering -- Mathematical models; Parameter estimation; Mathematical models; Electronic books